2018
DOI: 10.1088/1538-3873/aaa53f
|View full text |Cite
|
Sign up to set email alerts
|

The SED Machine: A Robotic Spectrograph for Fast Transient Classification

Abstract: Current time domain facilities are finding several hundreds of transient astronomical events a year. The discovery rate is expected to increase in the future as soon as new surveys such as the Zwicky Transient Facility (ZTF) and the Large Synoptic Sky Survey (LSST) come on line. At the present time, the rate at which transients are classified is approximately one order or magnitude lower than the discovery rate, leading to an increasing "follow-up drought". Existing telescopes with moderate aperture can help a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
167
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 203 publications
(174 citation statements)
references
References 31 publications
2
167
0
Order By: Relevance
“…We found that the Balmer lines of ZTF18aahiqfi, ZTF18aaidlyq, and ZTF18aasuray had gotten dramatically stronger and broader compared to archival SDSS spectra of their hosts, obtained more than a decade prior (in April 2003, Dec 2002, and Feb 2001. ZTF18aasszwr and ZTF18aaabltn showed similar striking spectral changes when they were followed up on 2018 Dec 3 and 9 using the Spectral Energy Distribution Machine (SEDM; Blagorodnova et al 2018a) IFU spectrograph on the Palomar 60-inch (P60; Cenko et al 2006) operating as part of ZTF. Both displayed broader emission lines and bluer continuua compared to archival LINER spectra (from Feb 2007 andJun 2004, respectively).…”
Section: Optical Spectroscopymentioning
confidence: 90%
“…We found that the Balmer lines of ZTF18aahiqfi, ZTF18aaidlyq, and ZTF18aasuray had gotten dramatically stronger and broader compared to archival SDSS spectra of their hosts, obtained more than a decade prior (in April 2003, Dec 2002, and Feb 2001. ZTF18aasszwr and ZTF18aaabltn showed similar striking spectral changes when they were followed up on 2018 Dec 3 and 9 using the Spectral Energy Distribution Machine (SEDM; Blagorodnova et al 2018a) IFU spectrograph on the Palomar 60-inch (P60; Cenko et al 2006) operating as part of ZTF. Both displayed broader emission lines and bluer continuua compared to archival LINER spectra (from Feb 2007 andJun 2004, respectively).…”
Section: Optical Spectroscopymentioning
confidence: 90%
“…An important instrument for photometric follow-up observations during PTF/iPTF was the 1.52-m telescope (known as P60) at Palomar Observatory. The telescope was used for imaging with the GRBCam camera (Cenko et al 2006) or the Spectral Energy Distribution Machine (SEDM) integral field spectrograph (Blagorodnova et al 2018) using SDSS gri filters. A typical strategy with the P60 was to obtain SDSS gri images of a SN field with a cadence of 1 d or 3 d (for young SNe) and a cadence of 6 d for older SNe.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…The advent of such large SN surveys has prompted the development of high throughput low to medium resolution spectrographs like the SED Machine [145] and FLOYDS [146] to classify SNe in large numbers. However, more such instruments on larger aperture telescopes are needed for the LSST era.…”
Section: The Future: Bright Fast and Abundantmentioning
confidence: 99%